2018
DOI: 10.1093/mnras/sty1988
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of the UV upturn: z = 0.3, 0.55, and 0.7

Abstract: We have analysed the strength of the UV upturn in red sequence galaxies with luminosities reaching to below the L * point within four clusters at z = 0.3, 0.55 & 0.7. We find that the incidence and strength of the upturn remains constant up to z = 0.55. In comparison, the prevalence and strength of the UV upturn is significantly diminished in the z = 0.7 cluster, implying that the stellar population responsible for the upturn in a typical red sequence galaxy is only just developing at this redshift and is esse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
2
20
1
Order By: Relevance
“…Using the YEPS Stellar Population Synthesis models of Chung et al (2017) that incorporate He-enhancement, Y ≥ 0.39 is predicted (assuming solar metallicity and z f = 4) to account for the full range in FUV − r and NUV − r colours seen in all of these clusters below z = 0.1 (note that metallicity, unless highly subsolar, which is not the case for these galaxies, does not strongly affect the HB morphology and therefore the UV colours for passive galaxies, so the observed range in colours cannot be accounted for my metal abundance). Consistent with the observations of Ali et al (2018c), these models predict that the (2017). Galaxies with NUV − r > 5.4 are convincingly passive systems, while those with 5.0 < NUV − r < 5.4 may still contain some residual star formation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Using the YEPS Stellar Population Synthesis models of Chung et al (2017) that incorporate He-enhancement, Y ≥ 0.39 is predicted (assuming solar metallicity and z f = 4) to account for the full range in FUV − r and NUV − r colours seen in all of these clusters below z = 0.1 (note that metallicity, unless highly subsolar, which is not the case for these galaxies, does not strongly affect the HB morphology and therefore the UV colours for passive galaxies, so the observed range in colours cannot be accounted for my metal abundance). Consistent with the observations of Ali et al (2018c), these models predict that the (2017). Galaxies with NUV − r > 5.4 are convincingly passive systems, while those with 5.0 < NUV − r < 5.4 may still contain some residual star formation.…”
Section: Discussionsupporting
confidence: 76%
“…UV upturn colour is nearly constant to z ≈ 0.6 (depending on Y and the epoch at which the stars were formed) and then evolves rapidly to the red. This is indeed observed in a z = 0.7 cluster (Ali et al 2018c). It is also interesting that the bluest UV upturn colours tend to occur among the most massive galaxies, which also tend to be older and more metal rich (Smith et al 2012b).…”
Section: Discussionmentioning
confidence: 52%
“…Note that these ages are determined by the total light, so do not necessarily reflect the age of the oldest stars, the UV upturn in particular being expected to result from HB stars at least 8 Gyr old (e.g. Kaviraj et al 2007b;Ali et al 2018c). 5 For the star formation time-scale, τ (middle panel), we again see that the bulk of the eliminated pink points (and most of the red circles, the galaxies which failed the WISE cut) tend to lie at larger values, consistent with longer lasting star formation, while the black points, our best (NUV + WISE red sequence) sample, generally ran down their star formation on time-scales 1-2 Gyr.…”
Section: A D D I T I O Na L P Ro P E Rt I E S O F U P T U R N G a L Amentioning
confidence: 99%
“…Recently Ali et al published a series of papers revisiting the UV upturn discussion (Ali et al 2018a,b,c;Ali et al 2019) as well as Boissier et al (2018). To explore the evolution of the UV upturn, Ali et al (2018c) selected data from four galaxy clusters (one at z ≈ 0.31, two at z ≈ 0.55, and one at z ≈ 0.68), retrieved from the Hubble Space Telescope (HST) Legacy Archive 1 ; they concluded that the incidence of the phenomenon rises up until z ≈ 0.55 and then it strongly declines, suggesting that, in fact, the UV upturn depends on redshift.…”
Section: Introductionmentioning
confidence: 99%
“…Differently fromAli et al (2018c) -whom explored whether there was an evolution of the UV upturn by using selected systems located in four galaxy clusters in three distinct redshift bins (0.31, 0.55, 0.68) using HST archive Fraction ( f upturn ) of UV bright RSGs that foster the UV upturn phenomenon as a function of z, stratified by their emission-line classes. Projections of f upturn are displayed for four slices of log M , as shown in each corresponding x-axis.…”
mentioning
confidence: 99%